Inverse Approach to Evaluate the Tubular Material Parameters Using the Bulging Test - Yulong Ge; Xiaoxing Li; Lihui Lang (Advances in Materials Science and Engineering)
Tubular material parameters are required for both part manufactory process planning and finite element simulations. The bulging test is one of the most credible ways to detect the property parameters for tubular material. The inverse approach provides more effective access to the accurate material evaluation than with direct identifications. In this paper, a newly designed set of bulging test tools is introduced. An inverse procedure is adopted to determine the tubular material properties in Krupkowski-Swift constitutive model of material deformation using a hybrid algorithm that combines the differential evolution and Levenberg-Marquardt algorithms. The constitutive model’s parameters obtained from the conventional and inverse methods are compared, and this comparison shows that the inverse approach is able to offer more information with higher reliability and can simplify the test equipment.